2013
DOI: 10.1097/cad.0b013e3283610b5d
|View full text |Cite
|
Sign up to set email alerts
|

Pegylated filgrastim is comparable with filgrastim as support for commonly used chemotherapy regimens

Abstract: The purpose of this study was to compare the efficacy and safety of a single subcutaneous injection of pegylated filgrastim with daily filgrastim as a prophylaxis for neutropenia induced by commonly used chemotherapy regimens. Fifteen centers enrolled 337 chemotherapy-naive cancer patients with normal bone marrow function. All patients randomized into AOB and BOA arms received two cycles of chemotherapy. Patients received a single dose of pegylated filgrastim 100 µg/kg in cycle 1 (AOB) or cycle 2 (BOA) and dai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 15 publications
0
32
0
Order By: Relevance
“…In brief, this study demonstrated that two weekly injections of PEGfilgrastim are equivalent or significantly better in virtually all parameters reflecting enhanced granulopoiesis compared to 17-21 days of daily filgrastim injections. A single sc injection of pegylated filgrastim provides adequate and safe neutrophil support, comparable to daily sc injections of filgrastim, in human patients receiving myelosuppressive chemotherapy [90].…”
Section: Studies With Pegylated G-csfmentioning
confidence: 99%
“…In brief, this study demonstrated that two weekly injections of PEGfilgrastim are equivalent or significantly better in virtually all parameters reflecting enhanced granulopoiesis compared to 17-21 days of daily filgrastim injections. A single sc injection of pegylated filgrastim provides adequate and safe neutrophil support, comparable to daily sc injections of filgrastim, in human patients receiving myelosuppressive chemotherapy [90].…”
Section: Studies With Pegylated G-csfmentioning
confidence: 99%
“…FN was assumed to require hospitalization and the mortality rate due to FN was set to 9.5% across all G-CSF regimens based on prior literature linking mortality to FN (Kuderer et al, 2006). As there were no recent comparative data available, the chemotherapy delay rate for lipegfilgrastim was also applied to filgrastim and pegfilgrastim as a percentage of the SN rate (Bondarenko et al, 2013;Buchner et al, 2014;Volovat et al, 2015) Pegfilgrastim (Bondarenko et al, 2013;Volovat et al, 2015) Filgrastim (Holmes et al, 2002a;Holmes et al, 2002b;Green et al, 2003;Grigg et al, 2003;Vose et al, 2003;Bondarenko et al, 2013;Park et al, 2013;Shi et al, 2013;Volovat et al, 2015) Severe neutropenia (cycle 1 / cycles 2-4) Market share (Budget Impact Analysis only) Marketplace dynamics are critical to budget impact models in terms of existing product utilization and the effect of the new treatment on this utilization, including the rate of adoption following introduction. The budget impact of including lipegfilgrastim on the Brazilian national formulary was estimated by comparing the pre-lipegfilgrastim reference scenario with the post-lipegfilgrastim new scenario.…”
Section: Clinical Parameters and Survival Estimatesmentioning
confidence: 99%
“…However, there have been some reports about the varying effects of S-G-CSF and L-G-CSF drugs in reducing FN and SN incidence rate after chemotherapy [11][12][13][14]. Multiple studies have indicated that pegfilgrastim is more effective than filgrastim based on ANC evaluation in patients receiving myelosuppressive chemotherapy [11,12,[15][16][17][18][19][20][21][22][23][24][25][26][27][28]. Thus, there are differing accounts about the benefits of S-G-CSF and L-G-CSF drugs and the subject requires further clarification.…”
Section: Introductionmentioning
confidence: 99%
“…2008 [26] Germany BC I/ II/ III/ IV TAC Pegfilgrastim v 17 Bozzoli et al 2015 [27] Italy DLBCL I/ II/ III/ IV CHOP+rituximab Pegfilgrastim v 18 Filon et al 2015 [13] Russia BC II/ III/ IV DA Empegfilgrasti Figures Figure 1 Flow chart depicting study selection process.…”
mentioning
confidence: 99%